The Rules Of Dotting Letters In Early Islamic Inscriptions/ قواعد النقط في النقوش الإسلامية المبكرة - Aloufi, Sultan Awwad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research unravels the rules of dotting letters and its characteristics in the Hijazi script stage, an essential stage of Arabic writing, employing the writings contained in the Hijaz inscriptions in the first three Hijri centuries, a period that is described as the period of early Islamic inscriptions, during which that script became developed and widespread, keeping pace with the emergence of the ancient Islamic civilization and its development. The research adopted the descriptive approach to explain the dotted letters, how they are dotted, and the various features used in dotting. The main results of the study were represented in several points, namely, revealing the rules and foundations of punctuation in the early stage of writing in the first three Hijri centuries, creating an illustrated reference that demonstrates this, and comparing it with the rules of punctuation used today, to fill the gap in one aspect of punctuation and its development in Arabic writing and to be a reference for those interested in the development of Arabic writing in general, and those interested in the history of punctuation and its issues in particular.